KOMPARASI MODEL PENEMUAN TERBIMBING DAN PEMBELAJARAN LANGSUNG TERHADAP KEMAMPUAN PEMBUKTIAN MATEMATIS - Jamilah Jamilah; Hartono Hartono; Utin Desy Susiaty (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The aims of this study were to investigate: (1) in indicator 1, which provides better mathematical proofing capability, guided discovery model or direct learning; (2) in indicator 2, which provides better mathematical proofing capabilities, guided discovery models or direct learning; (3) which provides better mathematical proofing capabilities, guided discovery models or direct learning. This research is a quantitative with the population of all students of semester VI Mathematics Education Study Program IKIP PGRI Pontianak. Sampling was done by cluster random sampling technique. Data collection techniques are measurement. Test the research hypothesis using t test. Based on these results it can be concluded as follows. (1) In indicator 1, mathematical proofing ability with guided discovery model is not better than direct learning. (2) In indicator 2, mathematical proof capability with guided discovery model is not better than direct learning. (3) The ability of mathematical proof with guided discovery model is not better than direct learning.